Functional studies of CpSRP54 in diatoms show that the mechanism of thylakoid protein insertion differs from that in plants and green algae. (16th February 2021) - Nymark, Marianne; Grønbech Hafskjold, Marthe Caroline; Volpe, Charlotte; Fonseca, Davi de Miranda; Sharma, Animesh; Tsirvouli, Eirini; Serif, Manuel; Winge, Per; Finazzi, Giovanni; Bones, Atle Magnar
SUMMARY: The chloroplast signal recognition particle 54 kDa (CpSRP54) protein is a member of the CpSRP pathway known to target proteins to thylakoid membranes in plants and green algae. Loss of CpSRP54 in the marine diatom Phaeodactylum tricornutum lowers the accumulation of a selection of chloroplast‐encoded subunits of photosynthetic complexes, indicating a role in the co‐translational part of the CpSRP pathway. In contrast to plants and green algae, absence of CpSRP54 does not have a negative effect on the content of light‐harvesting antenna complex proteins and pigments in P. tricornutum, indicating that the diatom CpSRP54 protein has not evolved to function in the post‐translational part of the CpSRP pathway. Cpsrp54 KO mutants display altered photophysiological responses, with a stronger induction of photoprotective mechanisms and lower growth rates compared to wild type when exposed to increased light intensities. Nonetheless, their phenotype is relatively mild, thanks to the activation of mechanisms alleviating the loss of CpSRP54, involving upregulation of chaperones. We conclude that plants, green algae, and diatoms have evolved differences in the pathways for co‐translational and post‐translational insertion of proteins into the thylakoid membranes. Significance Statement: Loss of diatom CpSRP54 results in altered photophysiological responses and lower levels of chloroplast‐encoded subunits of photosynthetic complexes, but in contrast to plants and green microalgae, absence of CpSRP54 does not have a negative impact on the level of light‐harvesting complex proteins and pigments in diatoms. By characterizing cpsrp54 KO lines in diatoms, we show that knowledge from the green lineage is not directly transferable to other groups of photosynthetic organisms.